Linking carbon emission and economic growth: Case from developing economies of the Asian region. Issue 4 (13th December 2021) - Kumar, Smriti; Kumar, Harsh; Bhatia, Meena
Abstract: As an indicator of environmental quality, carbon dioxide (CO2 ) emission has gained much attention in the pre‐existing pieces of literature. Because of their complex link with economic development, human activities, etc., it's always being an issue of discussion and is largely neglected in the country's political decision‐making. The present study probes the association between economic growth and carbon dioxide emission in the context of developing nations in the Asian region, by incorporating urbanization, merchandise trade, Foreign Direct Investment and renewable energy consumption for the period of 10 years (i.e., 2009–2018). For the analysis, the Granger causality relationship is used with an appropriate panel data regression model. The results of the causality analysis indicate that there prevails a relationship running from economic growth, merchandise trade to CO2 emissions, whereas renewable energy consumption has an inverse and significant impact on CO2 emissions. Therefore, to enhance the environmental quality, more renewable energy sources should be used which helps in the betterment of human welfare. To overcome the problem of CO2 emission and tackling climate change has become an essential part of the national as well as international climate policy agenda.